Development of acute toxicity quantitative structure activity relationships (QSAR) and their use in linear alkylbenzene sulfonate species sensitivity distributions. (July 2016) - Belanger, Scott E.; Brill, Jessica L.; Rawlings, Jane M.; Price, Brad B.
Abstract: Linear Alkylbenzene Sulfonate (LAS) is high tonnage and widely dispersed anionic surfactant used by the consumer products sector. A range of homologous structures are used in laundry applications that differ primarily on the length of the hydrophobic alkyl chain. This research summarizes the development of a set of acute toxicity QSARs (Quantitative Structure Activity Relationships) for fathead minnows ( Pimephales promelas ) and daphnids ( Daphnia magna, Ceriodaphnia dubia ) using accepted test guideline approaches. A series of studies on pure chain length LAS from C10 to C14 were used to develop the QSARs and the robustness of the QSARs was tested by evaluation of two technical mixtures of differing compositions. All QSARs were high quality (R 2 were 0.965–0.997, p < 0.0001). Toxicity normalization employing QSARs is used to interpret a broader array of tests on LAS chain length materials to a diverse group of test organisms with the objective of developing Species Sensitivity Distributions (SSDs) for various chain lengths of interest. Mixtures include environmental distributions measured from exposure monitoring surveys of wastewater effluents, various commercial mixtures, or specific chain lengths. SSD 5th percentile hazardous concentrations (HC5s) ranged from 0.129 to 0.254 mg/L for wastewater effluents containing an average of 11.26–12 alkyl carbons. The SSDs are considered highly robust given the breadth of species (n = 19), use of most sensitive endpoints from true chronic studies and the quality of the underlying statistical properties of the SSD itself. The data continue to indicate a low hazard to the environment relative to expected environmental concentrations. Graphical abstract: Highlights: New single species QSARs for the anionic surfactant LAS are developed and verified. The new QSARs are applied to normalize diverse chronic toxicity data to relevant hazard assessment scenarios. Single Species Sensitivity Distributions (SSDs) are determined and compared to mesocosm findings. SSDs are somewhat conservative compared to robust stream mesocosm results. Integrated use of QSARs, normalization and SSD formulation provides a flexible method for environmental hazard determination.